"Ngedeso": Pengembangan Desa Pariwisata Berbasis Edukasi Sosial Budaya Yang Terintegrasi Sebagai Upaya Pemberdayaan Potensi Desa Gunungronggo - Fiddin, Faza Abdurahman; Utami, Anisa Nur (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2020)
Indonesia is a country that has the potential of natural resources, human resources, and culture that can be developed optimally. Improving the welfare and economy of the village is a challenge that is faced until now. An economy that is experiencing an increase in a village can determine the rate of development of the village. One village that has the potential to be developed, Gunungronggo village, is one of the villages located in the city of Malang with a population of 1907 households with a low economic level, because most of them work as small farmers. In addition, as many as 17% or 226 families of the Gunungronggo villagers are elderly and the majority live alone with relatively low incomes. The village financial source comes from the Village Fund Allocation (ADD) which is a significant fund for the Village to support village programs. One of the objectives of the Village Fund Allocation (ADD) is poverty alleviation (Minister of Home Affairs Regulation Number 37 of 2007). However, along with the large amount of Village Funds, the problem of poverty is still difficult to solve, therefore it still needs development for the welfare of the village. In addition, this village has other potentials that can be developed such as tourist attractions and local food diversity. Innovations that can be offered in the form of "NgeDeso", is an e-commerce application that integrates all activities carried out in the village as a solution to increase the level of the village economy by utilizing all local village communities. The objectives of this paper are 1) Optimizing the potential of the elderly in Gunungronggo village and 2) Introducing tourism, culture and local products typical of Gunungronggo. The Writing Method is used in this paper with participatory observation, in-depth interviews, and document review added.Â